Dampak Pendidikan dan Pelatihan Manajemen oleh Perpusnas terhadap Kinerja Pustakawan - Dedi Junaedi; Abdul Rahman Saleh; Khosy Alfin Maulana; Muhammad Ansyari Tantawi (Perpustakaan IPB, 2022)
Introduction. Indonesia has about 5 thousand librarians registered with the National Library. The condition of the librarian's competence varies greatly. The National Library of Indonesia has conducted training for competency improvement, but its success is not yet known. To determine the effectiveness of the training, this research was conducted. Research methods. This research is a survey research. The sample is a librarian who received management training from the National Library of Indonesia. The sample was drawn based on purposive sampling with a three-year limit of participants, namely 2017, 2018, and 2019. The questionnaire was made using a google survey. The incoming data is then tabulated, processed and analyzed. Results and Discussion. A total of 34 respondents (91.89%) think that management training is very useful. Twenty-nine respondents (78.38%) felt that 2 weeks was sufficient time for training. The training subject